A Mapping of Islamization of Accounting - Nurika Restuningdiah; Vega Wafaretta; Rizka Furqorina (Tazkia Islamic Finance and Business Review, 2019)
This article (Restuningdiah, 2019) has been retracted by the publisher. The author has submitted the same article to two journals at the same time (double publication).